Análise da dinâmica dos preços das terras rurais do município de Francisco Beltrão-PR - Mello, Juvenir de (2017)
The dissertation analyzes determinants of price dynamics of agricultural land in Francisco Beltrão-PR from 2000 to 2015. The price data of these lands were acquired from information of the Department of Rural Economy of the State of Paraná (DERAL) and interview. Starting with the historical process of formation of the Southwest region of Paraná, since lands titration until its respective valorization. The price of agricultural land are determined by a juncture of factors that are related in local, national and international scales. Because of specific attributes that the Brazilian land market possesses, it is considered that each site holds specific elements to get to the final pricing. The advent of the modernization process is also studied, since the state programs to promote the agricultural development, the financial credits and the impacts of economic policies on the land market through the past four decades. In conclusion, the idea is to analyze land prices of different rural communities of Francisco Beltrão, synthesizing the acquired dada between the properties, rated prices, developed activities and the characteristics of the ground.